Elevated Biomarkers of NETosis in the Serum of Pediatric Patients With Type 1 Diabetes and Their First-Degree Relatives - Klocperk, Adam; Vcelakova, Jana; Vrabcova, Petra; Zentsova, Irena; Petruzelkova, Lenka; Sumnik, Zdenek; Pruhova, Stepanka; Sediva, Anna; Parackova, Zuzana (Frontiers in immunology, 2021)
Type 1 diabetes (T1D) is an autoimmune disorder with unambiguous involvement of both innate and adaptive immune mechanisms in the destruction of pancreatic beta cells. Recent evidence demonstrated that neutrophils infiltrate the pancreas prior to disease onset and therein extrude neutrophil extracellular traps (NETs), web-like structures of DNA and nuclear proteins with a strong pro-inflammatory biologic activity. Our previous work showed that T1D NETs activate dendritic cells, which consequently induce IFNγ-producing Th1 lymphocytes. The aim of this study was to assess direct ex vivo biomarkers of NETosis in the serum of recent onset and long-term pediatric T1D patients, their first-degree relatives and healthy controls. To this end we evaluated serum levels of myeloperoxidase (MPO), neutrophil elastase (NE), proteinase 3 (PR3), protein arginine deiminase 4 (PAD4), LL37 and cell-free DNA-histone complexes in sex- and age-matched cohorts of T1D first-degree relatives, recent-onset T1D patients, and in patients 12 months after clinical manifestation of the disease. Our data shows that disease onset is accompanied by peripheral neutrophilia and significant elevation of MPO, NE, PR3, PAD4 and cell-free DNA-histone complexes. Most biomarkers subsequently decrease but do not always normalize in long-term patients. First-degree relatives displayed an intermediate phenotype, except for remarkably high levels of LL37. Together, this report provides evidence for the presence of ongoing NETosis in pediatric patients with T1D at time of clinical manifestation of the disease, which partly subsides in subsequent years.
Keywords: neutrophil extracellular trap; neutrophils; diabetes mellitus 1. typu; mladiství; mužské pohlaví; type 1 diabetes; Neutrophils; Adult; mladý dospělý; dítě; Child; PAD4; Diabetes Mellitus, Type 1; Child, Preschool; Young Adult; ženské pohlaví; ELISA; NETosis; NET; Humans; předškolní dítě; biologické markery; Extracellular Traps; neutrofily; extracelulární pasti; dospělí; Biomarkers; Female; Adolescent; lidé; Male; pediatric